Replication patterns of multiple plasmids coexisting in Escherichia coli. - Leonard, A C (1988)
The replication patterns of several plasmids were measured simultaneously during the cell division cycle of Escherichia coli B/r. F plasmids harboring oriS, both oriS and oriV, pSC101, and pBR322 were found to replicate at all stages of the cell division cycle with kinetics which were indistinguishable from one another and clearly different from the periodic synthesis of the minichromosomes pAL49 and pAL70.